Career indecision: a cross-sectional survey among students of National Youth Skills Training Institutes - Mansor, Maznizam; Mat Rashid, Abdullah (IDOSI Publications, 2013)
The purpose of this study is to compare several factors namely gender, academic achievement, working experiences and participation in career intervention programs on career indecision among students of one Malaysia premier skills training institution that offers various technical and vocational programs. Career indecision is measured by Career Factors Inventory (CFI) that was adapted from Chartrand, Robbins, Morril and Boggs. The inventory contains four factors which are two information factors and two personal emotional factors. The information factors are Need for Career Information (NCI) and Need for Self-Knowledge (NSK). The others two personal emotional factors are Career Choice Anxiety (CCA) and Generalized Indecisiveness (GI). The survey is conducted to 292 students that were randomly selected from a National Youth Skills Training Institute (IKBN) in the state of Selangor, Malaysia. Data is analyzed by descriptive and inferential statistics with utilized of SPSS program. The finding shows career indecision among students is at high level. Furthermore, it shows no difference between gender, academic achievement, working experiences and participation in career intervention programs on student’s career indecision. Several suggestions are made in improving career indecision among students in IKBN.